Salvation and Suicide: What Does Islamic Theology Say? - Anees, Munawar A. (Dialog, 2006)
The Islamic soteriological doctrine advocates good deeds and God's mercy as the pre-requisites for human salvation. This article introduces these two important dimensions of the Muslim belief of salvation. In contemporary settings it addresses some of the motives behind the spate of suicide bombings by Muslims and argues that taking one's own life is totally forbidden in Islam. The moving notion that suicide bombing is an open door to salvation is, therefore, untenable. Whatever the mitigating factors, there is no legitimacy in Islamic Law (shariah) to the crime of suicide or the derived terrorism.